Decoding "University War (대학전쟁)": STEM Education and Cultural Influence - Maspul, Kurniawan Arif; Melinda, Yona; Chemistry, Valerie Indiana; Wisudayanti, Karila; Fedora, Fedora; Rochmah, Dwi Febriana (Jurnal Psikologi, 2024)
University War (대학전쟁)" presents a captivating intersection of psychological, educational, and cultural dimensions within the context of STEM (Science, Technology, Engineering, and Mathematics) education. The Korean television show phenomenon engages viewers worldwide, transcending cultural boundaries with its gripping narrative of intellectual competition among South Korea's elite universities. Through psychological theories such as Bandura's social learning theory and Deci and Ryan's self-determination theory, the show underscores the significance of academic excellence and the intrinsic motivation driving contestants. Moreover, "University War" promotes critical thinking and problem-solving skills essential for STEM fields, reflecting broader societal attitudes toward education and career aspirations. As educators explore ways to sustain interest in STEM among K-Pop wave culture enthusiasts through initiatives inspired by the series, University War stands as a compelling case study highlighting the transformative potential of popular media in shaping educational outcomes and societal perceptions in the digital age.